2022
DOI: 10.1021/acsami.2c14574
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Distribution of Nafion Ionomer Thin Films on Nitrogen-Modified Carbon Surfaces

Abstract: Chemically modified carbon supports for the cathode catalyst layers of polymer electrolyte fuel cells (PEFCs) show considerable promise for boosting the oxygen reduction reaction. This study evaluated the ionomer distribution of Nafion ionomer thin films on nitrogen (N)modified carbon surfaces along their depth direction. Neutron reflectivity (NR) measurements performed using the double-contrast technique with H 2 O and D 2 O revealed that the introduction of N functional groups to carbon thin films promoted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…The carbon-dense layer region (∼0.75 nm in thickness) exhibits a remarkably higher density due to the interactions with the carbon support, which is approximately 1.5 times higher than that in the bulk region. Experiments results revealed that Nafion self-assembles through its hydrophobic backbones on the graphitic surfaces of carbon supports due to the attractive interactions, thus forming the thin adsorption layer on the carbon surface with a significantly higher density. For the corresponding oxygen distribution in Figure c, it is highly concentrated in the carbon-dense layer regions of both SC and HSC supports, which suggests that those regions are capable of accumulating oxygen. Besides, it is noteworthy that oxygen accumulation also exists above the carbon-dense layer of HSC (about 0.75–1.5 nm in the z direction), while it is not conspicuous on the SC support as oxygen can be gradually consumed during the diffusion process.…”
Section: Resultsmentioning
confidence: 98%
“…The carbon-dense layer region (∼0.75 nm in thickness) exhibits a remarkably higher density due to the interactions with the carbon support, which is approximately 1.5 times higher than that in the bulk region. Experiments results revealed that Nafion self-assembles through its hydrophobic backbones on the graphitic surfaces of carbon supports due to the attractive interactions, thus forming the thin adsorption layer on the carbon surface with a significantly higher density. For the corresponding oxygen distribution in Figure c, it is highly concentrated in the carbon-dense layer regions of both SC and HSC supports, which suggests that those regions are capable of accumulating oxygen. Besides, it is noteworthy that oxygen accumulation also exists above the carbon-dense layer of HSC (about 0.75–1.5 nm in the z direction), while it is not conspicuous on the SC support as oxygen can be gradually consumed during the diffusion process.…”
Section: Resultsmentioning
confidence: 98%
“…They are amphiphilic materials with a backbone consisting of hydrophobic perfluorinated groups and hydrophilic side chains containing fluorocarbons, ether groups, and sulfonic acid at the ends. Although there is controversy regarding the adsorption morphology of ionomers on the catalyst surface, ,, side-chain adsorption onto Pt oxide is preferable; ,, the sulfonic acid can interact with hydrophilic groups via hydrogen bonding and electrostatic interactions with the functionalized support. , Thus, we considered that the dispersion and adsorption morphology of ionomers might have a great deal to do with the functional group and hydrophilic information obtained above.…”
Section: Resultsmentioning
confidence: 99%
“…It remains ambiguous as to which component of the catalyst surface, be it Pt or carbon, predominantly attracts the ionomer in each MEA. Nevertheless, several studies highlighting interactions between ionomers and carbon functional groups ,,, suggest that in the case of K-2, the ionomer has a greater tendency to adsorb on the carbon surface than is the case for K-3, attributed to the presence of a higher number of hydrophilic groups which can strongly interact with the −SO 3 – moiety. This tendency could potentially counteract Pt specific adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of generating the infinite chain ionomer was mainly based on previous work. 51 First, a linear straight ionomer chain with n monomer monomers infinitely connected by a periodic boundary was created, indicating that only one periodic ionomer chain exists in the system. We considered that the artifact of this approach is small, as the intertwined structure of multiple ionomers does not largely change in the time scale of the MD simulation.…”
Section: ■ Methodsmentioning
confidence: 99%